PERLINDUNGAN HUKUM TERHADAP PEMBELI RUMAH BERDASARKAN PERATURAN MENTERI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT NOMOR 11/PRT/M/2019 TENTANG SISTEM PERJANJIAN PENDAHULUAN JUAL BELI RUMAH - Muhammad Afif Ma’ruf (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTPPJB only contains standard clauses that usually benefit the seller, because the buyer's position is not free. Legal issues that occur and the facts that occur in the field is that developers often make fraud in terms of; use of green open space for building housing; does not provide an opportunity for consumers to study the deed of the Purchase Binding Agreement (PPJB).The problem raised in this paper is how the legal protection of home buyers based on Ministerial Regulation (Permen) PUPR Number 11 / PRT / M / 2019 and What are the legal conditions that must be owned by home developers in selling their products based on Ministerial Regulation (Permen) PUPR Number 11 / PRT / M / 2019.This type of research is Normative Juridical research that is conducted based on legal material and by collecting data, studying books in the library, and legislation relating to this research.The results of research Developer or developer of a legal entity that sells a single house, a series of houses and flats that are sold to the community by cash or credit, in terms of credit a lot of problems arise in terms of payment, broken promises, and incompatible development. Regulation of the Minister of Public Works and Public Housing Number 11 / PRT / M / 2019 Concerning the Preliminary Agreement on Buying and Selling Houses is present to provide a sense of security for consumers and give a fair impact to both parties who are engaged in binding the sale and purchase of houses. based on PUPR Minister Regulation Number 11 / PRT / M / 2019 article 4 paragraph (1)